Chemical regeneration of granular activated carbon: preliminary evaluation of alternative regenerant solutions - Larasati,A; Fowler,GD; Graham,NJD (Environmental Science: Water Research & Technology, 2020)
Granular activated carbon (GAC) is used in drinking water treatment plants worldwide to remove micro-pollutants such as pesticides. Early breakthrough of problematic micro-pollutants leads to frequent and costly thermal regeneration off-site. A potential alternative approach is to chemically regenerate GAC on-site (possibly in situ) with an appropriate solution capable of desorbing organic contaminants, having a range of physico-chemical properties. In this study, four types of regenerant solution were evaluated in batch tests for their ability to desorb five target contaminants. The solutions were: high purity water, sodium hydroxide, ethanol, and a mixture of sodium hydroxide and ethanol. The contaminants included: phenol and nitrobenzene, as representative aromatic compounds; clopyralid and metaldehyde, as poorly-adsorbed pesticides; and isoproturon, a well-adsorbed pesticide. Among the properties of the contaminants, their hydrophobicity and aqueous solubility had the most significant influence on the desorption efficiency. NaOH/CH3CH2OH was found to be more effective than individual solutions in desorbing the target contaminants, indicating an ability to desorb both hydrophobic and hydrophilic compounds. The NaOH/CH3CH2OH regenerant solution yielded desorption efficiencies in the range of approximately 40–90%, with the efficiency dependent on the contaminant. A thermodynamic study provided valuable fundamental information regarding the adsorption and desorption mechanisms, and the existence of two binding sites involving a weak physisorption and a stronger chemisorption-like interaction between the contaminants and the GAC.